Prevalence of otological symptoms at Rio Grande do Norte’s population - Bedaque, Henrique; Silveira, Yasmim Barros; Silva, Pedro Henrique de Medeiros; Ferreira, Lidiane Maria de Brito Macedo (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2023)
Otorhinolaryngology has several areas, including otology, rhinology, in addition to involving complaints of the throat, sleep, dysphagia, phoniatry, taste, smell and otoneurology. In terms of frequency in otorhinolaryngology outpatient clinics, right after nasal alterations, there are otological complaints. OBJECTIVE: Define the prevalence of hypoacusis, dizziness, tinnitus, otological pruritus and earache of Rio Grande do Norte’s population. METHOD: A total of 1067 volunteers at the Hospital Universitário Onofre Lopes (HUOL-RN) were evaluated regarding the presence of otological complaints. RESULTS AND CONCLUSION: Otological complaints are extremely common in the studied population, especially otological pruritus, hypoacusis and tinnitus.